Rozbudowa sieci kolejowej jako czynnik rozwoju aglomeracji łódzkiej do 1914 r. - Kulesza, Piotr (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
Disquisition on junction as a factor that forms progress of the Łódź agglomeration seems to be an extremely important topic for the study about this subject. Building the line connecting the city by the Warsaw-Vienna’s railway, and then Kaliska Railway gave Łódź a line with the most important market, but what's more, it made the most significant industry centre in the whole region. This article talks over the plans of the forward expansion of Łódź XIX/XX century junction, from which some part of them was unfortunately unrealized. It gave evidence of the action character and the swing of the Łódź industry group on the front with Juliusz Kunitzer, courageously competing with the groups connected with Russian capital. The most interesting project, which came by only partial realization, was obviously a bypass railway building, which was supposed to reduce the cost of the transportation and material depot. It gave the possibility to build the branches to Pabianice, Zgierz and other cities of the region, but it wasn’t exploited because of the strategical points. Building the line turned into north side, connecting Łódź with Prussia, which had given a chance to develop of the cities such as Ozorków or Łęczyca, was unrealized either. Similar plans of constructing the line turned into south side, to connect directly Łódź with Silesia were also torpedoed by the Russian authorities. These are only examples of thinking about Łódź as an agglomeration centre, which show how big potential that city and region had. This is an evidence of how the communication became one of the most important factor forming Łódź agglomeration giving a possibility to develop particular smaller and bigger urban centre, accelerating the changes of a spatial management character of the suburban Łódź areas.